O extrato etanólico da planta medicinal Combretum leprosum previne déficits cognitivos em um modelo murino de isquemia cerebral global - Ferreira, Glenda Gomes (2019)
Stroke (AVE) is described as one of the main causes of death according to the World Health Organization (WHO). The AVE is subdivided into ischemic (AVEi) and hemorrhagic (AVEh), the first being more prevalent. The interruption of blood in a particular region of the brain in the AVEi creates two distinct regions in the tissue: the "ischemic nucleus" and the "ischemic penumbra". The cells of the ischemic nucleus are first affected from necrosis due to the direct lack of basic supplies for the cell survival, while cells in the penumbra region die from apoptosis, being this region feasible of intervention. Currently, the main pharmacological therapeutic approach involves the use of Alteplase, a thrombolytic drug that is extremely restricted. Thus, new approaches are needed to therapeutic spectrum, in addition to reducing the side effects. To this end, medicinal plants of the Brazilian flora are a powerful source for the development of medicines for the treatment of stroke. Given the above, our work evaluated the possible effect of the treatment with the ethanolic extract of the medicine plant Combretum leprosum (EECL) in preventing cellular and cognitive damage caused by AVEi in mice. Herein, in the present study, we used male mice of the Mus species musculus and Swiss lineage, 8-10 weeks (CEUA 53/2017 - UFES), which were submitted to a global ischemia / reperfusion (BCCAo) model and treated orally with EECL at the dose of 100mg / kg. The animals were randomly divided into four experimental groups: vehicle sham (saline + tween20) (SV), sham extract (saline + tween 20 + EECL) (SE), vehicle ischemia (IV) and ischemia extract (IE). After anesthesia recovery, the animals received two doses of EECL or vehicle at intervals of 3 hours between doses and this regimen was repeated 24 hours later. Subsequently, the dose became unique until the end of the experiments. The quantification of the infarct area showed a reduction of the ischemic area by 33%. Additionally, our data shows that the treatment decrease the cognitive deficits related to spatial memory and object recognition. The improvement found in the treatment of AVEi is possibly related to the increase of cells immunopositive for the neuronal marker NeuN in the Immunofluorescence assay in animals of the IE group, as well as the decrease of the expression of the marker of activated astrocytes GFAP in the same group. Overall, this report provides promising evidence of the potencial use of EECL in the treatment of stroke.